2018
DOI: 10.1538/expanim.17-0033
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of spinal nerve ligation-mediated functional activation of the rat brain using manganese-enhanced MRI

Abstract: To provide clear information on the cerebral regions according to peripheral neuropathy, the functional activation was investigated using manganese-enhanced magnetic resonance imaging (MEMRI). L5-spinal nerve ligation (SNL) was applied to the rats to induce neuropathic pain. Mechanical allodynia and thermal hyperalgesia were measured to confirm neuropathic pain induction following before and after gabapentin (GBP) treatment. The cerebral regions were investigated using a 4.7T MRI system in the sham, SNL, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Until now, the effects of mTOR inhibitor using animal MRI have not been studied. Several studies have used the MEMRI method to assess pain in the central nervous system or to observe changes in pain through analgesic use [4,10,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the effects of mTOR inhibitor using animal MRI have not been studied. Several studies have used the MEMRI method to assess pain in the central nervous system or to observe changes in pain through analgesic use [4,10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Since MEMRI studies were used to demonstrate the identifying pain pathways in the brain, various pain imaging studies have been performed in the spinal cord and brain [6,7]. Nerve injury [10] and thermal [11] stimulus-induced abnormal brain activities have been shown using MEMRI. In addition, our previous formalin-induced pain study also showed that MEMRI could be a good indicator of pain-induced changes in the CNS [7].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the effects of mTOR inhibitor using animal MRI have not been studied. Several studies have used the MEMRI method to assess pain in the central nervous system or to observe changes in pain through analgesic use [3,10,24]. However, the MEMRI method has several di culties in observing the effects of pain reduction or changes in neuronal activities.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental hyperalgesia produces the up-regulated neuronal activation of brain responses within pain-processing regions, including the anterior cingulate cortex (ACC), insular cortex (IC), and primary (SI) and secondary somatosensory cortices (SII) [7][8][9]. With MEMRI studies having been found useful in identifying pain pathways in the brain, various pain imaging studies have been performed in the spinal cord and brain [5,6], allowing researchers to visualize nerve injury [10] and thermal [11] stimulus-induced abnormal brain activities. Similarly, our previous formalininduced pain study also showed that MEMRI could be a good indicator of pain-induced changes in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the contralateral RSgA in the SNI model seems an important hub, which integrates the nociceptive information and works directly with numerous painrelated structures in a segregated network. Other studies have demonstrated an increase of the cerebral blood flow, BOLD, and manganese-enhanced signals within the retrosplenial cortex in different pain models, 10,26 suggesting that RSgA activation is conserved through different types of chronic pain. Moreover, aberrant DMN functioning in chronic pain patients has been reported with the functional connectivity between the PFC and the retrosplenial cortex (posterior cingulate) correlated with pain rumination, underlying their involvement in the emotional aspect of pain.…”
Section: The Retrosplenial Cortex As a Pain Integrator Structurementioning
confidence: 94%